Tuning and Sensitivity Enhancement of Surface Plasmon Resonance Biosensor With Graphene Covered Au-MoS 2-Au Films - Zhitao Lin; Leyong Jiang; Leiming Wu; Jun Guo; Xiaoyu Dai; Yuanjiang Xiang; Dianyuan Fan (IEEE Photonics Journal, 2016)
In the conventional surface plasmon resonance biosensor, the sensitivity using angular interrogation is low. Graphene/MoS2 has been attached on the metal surface to improve the sensitivity; however, the ability to improve sensitivity is limited. Here, by sandwiching the MoS2 sheets between two gold films in the Kretschmann configuration, we demonstrate an ultrasensitive surface plasmon resonance sensor. By optimizing the structure of sensor, we find that the sensitivity as high as 182°/RIU can be realized with 4-layers MoS2 and a monolayer graphene. Moreover, it is indicated that the sensitivity can be tuned and controlled by changing the layer numbers of graphene and MoS2.